Gd-EOB-DTPA-enhanced MRI for quantitative assessment of liver organ damage after partial hepatic ischaemia reperfusion injury: correlation with histology and serum biomarkers of liver cell injury. - Getzin, Tobias; Gueler, Faikah; Hartleben, Björn; Gutberlet, Marcel; Thorenz, Anja; Chen, Rongjun; Meier, Martin; Bräsen, Jan Hinrich; Derlin, Thorsten; Hartung, Dagmar; Lang, Hannah A. S.; Haller, Hermann; et al. (European Radiology, 2018)
Objective: To evaluate Gd-EOB-DTPA-enhanced MRI for quantitative assessment of liver organ damage after hepatic ischaemia reperfusion injury (IRI) in mice.Methods: Partial hepatic IRI was induced in C57Bl/6 mice (n = 31) for 35, 45, 60 and 90 min. Gd-EOB-DTPA-enhanced MRI was performed 1 day after surgery using a 3D-FLASH sequence. A subgroup of n = 9 animals with 60 min IRI underwent follow-up with MRI and histology 7 days after IRI. The total liver volume was determined by manual segmentation of the entire liver. The volume of functional, contrast-enhanced liver parenchyma was quantified by a region growing algorithm (visual threshold) and an automated segmentation (Otsu's method). The percentages of functional, contrast-enhanced and damaged non-enhanced parenchyma were calculated according to these volumes. MRI data was correlated with serum liver enzyme concentrations and histologically quantified organ damage using periodic acid-Schiff (PAS) staining.Results: The percentage of functional (contrasted) liver parenchyma decreased significantly with increasing ischaemia times (control, 94.4 ± 3.3%; 35 min IRI, 89.3 ± 4.1%; 45 min IRI, 87.9 ± 3.3%; 60 min IRI, 68 ± 10.5%, p < 0.001 vs. control; 90 min IRI, 55.9 ± 11.5%, p < 0.001 vs. control). The percentage of non-contrasted liver parenchyma correlated with histologically quantified liver organ damage (r = 0.637, p < 0.01) and serum liver enzyme elevations (AST r = 0.577, p < 0.01; ALT r = 0.536, p < 0.05). Follow-up MRI visualized recovery of functional liver parenchyma (71.5 ± 8.7% vs. 84 ± 2.1%, p < 0.05), consistent with less histological organ damage on day 7.Conclusion: We demonstrated the feasibility of Gd-EOB-DTPA-enhanced MRI for non-invasive quantification of damaged liver parenchyma following IRI in mice. This novel methodology may refine the characterization of liver disease and could have application in future studies targeting liver organ damage.Key Points: • Prolonged ischaemia times in partial liver IRI increase liver organ damage. • Gd-EOB-DTPA-enhanced MRI at hepatobiliary phase identifies damaged liver volume after hepatic IRI. • Damaged liver parenchyma quantified with MRI correlates with histological liver damage. • Hepatobiliary phase Gd-EOB-DTPA-enhanced MRI enables non-invasive assessment of recovery from liver injury.